Implementasi Kurikulum Merdeka Pada Mata Pelajaran Al Qur'an Hadis Kelas VII di MTs Negeri 3 Kebumen - Muflihatun Ni’mah; Agus Salim Chamidi (Tarbi: Jurnal Ilmiah Mahasiswa, 2026)
This study aims to describe the implementation process of the Independent Curriculum in the subject of Al-Qur'an Hadith Tajwid material for grade VII at MTs Negeri 3 Kebumen, as well as the obstacles, barriers and solutions faced. The research method used is descriptive qualitative with a field study approach. Research informants consisted of the Deputy Head of Curriculum and the Al-Qur'an Hadith teacher for grade VII. Data collection techniques include observation, interviews, and documentation, while data analysis uses the Miles and Huberman model including data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of the independent curriculum in learning Tajwid material begins with planning through analysis of Learning Outcomes (CP), preparation of Learning Objectives (TP) and Learning Objective Flow (ATP) through the MGMP forum in the district, compiling flexible teaching modules and planning differentiated learning. Learning activities include an introduction, core, and conclusion, as well as evaluation through assessment and reflection. P5RA is conducted outside of class hours. Implementation challenges include some teachers still using teacher-centered learning patterns and a lack of literacy in understanding the concept of the Independent Curriculum. Students face challenges in applying tajwid rules. The solution to address these challenges, among other challenges, is ongoing teacher development through workshops, training, and the Saturday Sharing forum. For students, these challenges are addressed through memorization programs, recitation of the Quran, recitation of the Quran, and Quran literacy activities